An empirical study juxtaposing the importance of implementing an e-participation model by the government for compliance intention and satisfaction level among Djiboutian generation z - Aden, Kadir (Journal of Governance and Administrative Reform, 2023)
Abstract   This research is among the very few studies seeking a focalized exploration of the impact of e-participation perception on satisfaction and compliance intention among the Djiboutian generation Z. To facilitate the task, our responders, which were encompassed of "n=469”; were requested to share their views about perceived accountability (PA), perceived transparency (PT), perceived quality deliverance (PQD) as well as how perceived sustainably innovative (PSI) their perception was when the current government embraces virtual community participatory platforms (EP). To answer the research objective and analyze the highly complex data, this research performed a structural equation model (SEM) by using Amos software. The finding projected that both perception accountability (PA) and perception transparency (PT) seldom influence compliance intention and have a negative effect, whereas only PT contributes positively to satisfaction among the z generation, thus further highlighting the complex status of compliance. On the other hand, PQD and PSI have a significant positive influence on Djibouti generation z compliance and satisfaction likelihood. It is hoped the empirical evidence of this research will provide the Djiboutian authority that an all-of-society approach incorporated with technology will enhance the government's quality deliverance, at the same time, shape youth's perception toward their representative and infuse a sustainable, healthy society based on collective cooperation and social cohesion.   Keywords: e-participation adoption, generation z, compliance intention, open government partnership, co-creation, SEM approach   Abstrak   Penelitian ini adalah salah satu dari sedikit studi yang mencari eksplorasi fokus dampak persepsi e-partisipasi terhadap kepuasan dan niat kepatuhan di antara generasi Z Djibouti. Untuk memfasilitasi tugas, responden kami terdiri dari "n=469”; diminta untuk berbagi pandangan mereka tentang persepsi akuntabilitas (PA), persepsi transparansi (PT), persepsi kualitas pengiriman (PQD) serta bagaimana persepsi inovasi berkelanjutan (PSI) persepsi mereka ketika pemerintah saat ini merangkul platform partisipasi komunitas virtual (EP). Untuk menjawab tujuan penelitian dan menganalisis data yang sangat kompleks, penelitian ini melakukan model persamaan struktural (SEM) dengan menggunakan perangkat lunak Amos. Temuan memproyeksikan bahwa akuntabilitas persepsi (PA) dan transparansi persepsi (PT) jarang memengaruhi niat kepatuhan dan memiliki efek negatif, sedangkan hanya PT yang berkontribusi positif terhadap kepuasan di antara generasi z, ini semakin menyoroti status kepatuhan yang kompleks. Di sisi lain, PQD dan PSI memiliki pengaruh positif yang signifikan terhadap kepatuhan dan kemungkinan kepuasan Djibouti generation z. Diharapkan bukti empiris dari penelitian ini akan memberikan otoritas Djibouti bahwa pendekatan semua masyarakat yang digabungkan dengan teknologi akan meningkatkan kualitas pemerintah, pada saat yang sama, membentuk persepsi pemuda terhadap perwakilan mereka, dan menanamkan pembangunan yang sehat dan berkelanjutan. masyarakat berdasarkan kerjasama kolektif dan kohesi sosial.   Kata kunci: adopsi e-partisipasi, generasi z, kepatuhan niat, kemitraan pemerintah terbuka, co-creation, pendekatan SEM